Epigenetic Regulation of Inflammatory Cytokines and Associated Genes in Human Malignancies - Rehana Yasmin; Sami Siraj; Amjad Hassan; Abdul Rehman Khan; Rashda Abbasi; Nafees Ahmad (Hindawi Limited, 2015)
Inflammation is a multifaceted defense response of immune system against infection. Chronic inflammation has been implicated as an imminent threat for major human malignancies and is directly linked to various steps involved in tumorigenesis. Inflammatory cytokines, interleukins, interferons, transforming growth factors, chemokines, and adhesion molecules have been associated with chronic inflammation. Numerous cytokines are reported to be aberrantly regulated by different epigenetic mechanisms like DNA methylation and histone modifications in tumor tissues, contributing to pathogenesis of tumor in multiple ways. Some of these cytokines also work as epigenetic regulators of other crucial genes in tumor biology, either directly or indirectly. Such regulations are reported in lung, breast, cervical, gastric, colorectal, pancreatic, prostate, and head and neck cancers. Epigenetics of inflammatory mediators in cancer is currently subject of extensive research. These investigations may help in understanding cancer biology and to develop effective therapeutic strategies. The purpose of this paper is to have a brief view of the aberrant regulation of inflammatory cytokines in human malignancies.